2011
DOI: 10.2139/ssrn.1741127
|View full text |Cite
|
Sign up to set email alerts
|

Regional Heterogeneity and Firms’ Innovation: The Role of Regional Factors in Industrial R&D in India

Abstract: This study makes an early attempt to estimate the magnitude and intensity of manufacturing firms' R&D by Indian states during the period 1991-2008 and analyses the role of regional factors on firm-level R&D activities. As there is little research on state-wise R&D performance of firms in India, this study serves an important contribution to the academic and policy realm. It has brought out the fact the total manufacturing R&D investment in India is unevenly distributed regionally with a few states accounting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
1
2
0
Order By: Relevance
“…A company's annual income, representing its size, access to digital assets, undertaking of sustainability concerns by its management, exposure to the international market through exports and undertaking of R&D expenditures are found to be positively associated with both its promotional expenses and the reported intangible value. A company's age is found to be negatively associated with both promotional Innovation and firm characteristics expenses and the reported intangible value, which remains consistent with earlier literature on innovation and firm-age (see Ghosh, 2009 andPradhan, 2011). Sargan's overidentifying restriction tests suggest that the restrictions are mostly valid.…”
Section: Robustness Checksupporting
confidence: 88%
See 1 more Smart Citation
“…A company's annual income, representing its size, access to digital assets, undertaking of sustainability concerns by its management, exposure to the international market through exports and undertaking of R&D expenditures are found to be positively associated with both its promotional expenses and the reported intangible value. A company's age is found to be negatively associated with both promotional Innovation and firm characteristics expenses and the reported intangible value, which remains consistent with earlier literature on innovation and firm-age (see Ghosh, 2009 andPradhan, 2011). Sargan's overidentifying restriction tests suggest that the restrictions are mostly valid.…”
Section: Robustness Checksupporting
confidence: 88%
“…Ghosh (2009) suggested that firms with larger size and export orientation have a higher probability of undertaking R&D activities, while firm age has an inverse relation with R&D activities. Pradhan (2011) found age, profit margin, foreign ownership and imported raw materials significantly affect the R&D activities of small and marginal enterprises. Lodh et al (2014) found that family ownership and business groups had a positive impact on innovation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most of the studies focus on the case of Asian multinational companies (MNCs), particularly studies that investigate OFDI from China and India (Buckley et al, M@n@gement 2015, vol. 18(1): 78-101 2007; Cheng & Ma, 2007;De Beule & Van Den Bulcke, 2012;Fung, Garcia-Herrera, & Siu, 2009;Kolstad & Wiig, 2012;Pradhan, 2011). Other studies are more focused on the effect of home country factors on OFDI and the performance of MNCs from emerging economies (Cuervo-Cazurra & Genc, 2011;He & Lin, 2012;Luo, Xue, & Han, 2009).…”
mentioning
confidence: 99%